Children's Orthographic Knowledge and Their Word Reading Skill: Testing Bidirectional Relations. (3rd July 2016) - Conrad, Nicole J.; Deacon, S. Hélène
ABSTRACT: Prominent models of word reading concur that the development of efficient word reading depends on the establishment of lexical orthographic representations in memory. In turn, word reading skills are conceptualised as supporting the development of these orthographic representations. As such, models of word reading development make clear predictions of bidirectional relations between lexical orthographic knowledge and word reading skill. We test these predictions in a longitudinal study of 112 English-speaking children in Grades 2 and 3. At two time points, we assessed lexical orthographic knowledge and three aspects of word reading skill: word reading accuracy, word reading efficiency, and phonological decoding. Consistent with theoretical predictions, we found that earlier word reading accuracy, word reading efficiency, and phonological decoding predicted gains in lexical orthographic knowledge. Contrary to theoretical predictions, lexical orthographic knowledge did not predict gains in any of our measured word reading skills.